SOCIO-ECONOMIC CHARACTERISTICS AND CONSTRAINTS OF SMALL-SCALE RICE FARMERS PARTICIPATION IN ANCHOR BORROWER PROGRAMME (ABP) IN JIGAWA STATE, NIGERIA - Ali, M. A.; Garba, A.; Sani R. M. (Nigerian Journal of Agriculture and Agricultural Technology, 2023)
The study examined the socio-economic characteristics and constraints of small-scale rice farmer’s participation in the Anchor Borrwer Programme (ABP) in Jigawa State, Nigeria. The specific objectives of this study were to, describe the socio-economics characteristics of the respondents and identify the constraints faced by the smallscale rice farmers in the study area. Multi-stage sampling techniques were employed to select 258 smallholder rice farmers. Data were collected using questionnaire and analyzed using descriptive statistics. The result shows that majority of the respondents are in active age, 20-30years (28.3%); in term of marital status, most of respondents 55.8% were married, 69.8% of the respondents were male and most of the respondents attented one form of formal education. The finding also revealed that about half 53.0% of the respondents were members of the cooperative society. The major constraints to participation of smallholder rice farmers in ABP as reported were, inadequate inputs, farmers level of education, land tenure system, and poor funding which were ranked 1st, 2nd, 2nd and 4th respectively. The programme has enhanced both income and outputs of the beneficiaries. It is recommended that; Federal Government should be consolidated on the gain of ABP in the state by increasing the fund for the programme in the state and make sure more smallscale rice farmers to benefit from the programme. Government and other stakeholders should encourage timely provision of inputs to ABP participants, other agricultural and financial institutions in the state should streamline their procedure for securing loans in order to make it easy to farmers.